DESIGNING THE SOVIET IDENTITY (THROUGH THE EXAMPLE OF ELYOR ISHMUKHAMEDOV’S FILMS TENDERNESS AND LOVERS) / КОНСТРУИРОВАНИЕ СОВЕТСКОЙ ИДЕНТИЧНОСТИ (НА ПРИМЕРЕ ФИЛЬМОВ Э. ИШМУХАМЕДОВА «НЕЖНОСТЬ» И «ВЛЮБЛЕННЫЕ») - SHCHEBROVA SVETLANA Ya. / ЩЕБРОВА СВЕТЛАНА ЯКОВЛЕВНА (Наука телевидения, 2020)
The article studies the Soviet identity, which fell into a crisis in the context of globalization and ethnic localization, gradually intensifying after the collapse of the USSR. In response to the decay of the Soviet mentality, it is necessary to understand how to overcome the split in society and make the process of cultural transformation under modernization conditions less painful for people. One of the mechanisms of forming the cultural identity of peoples is an appeal to the positive experience in common history. Simply copying the previous forms and means of forming cultural identity is impossible, since socio-economic foundations change; therefore, the problem needs a different solution. Exploring the Soviet past, one can understand which ideological values contributed to the consolidation of society in order to use this experience in construction of Russian civilizational identity. The purpose of the article is to study the films by Elyor Ishmukhamedov Tenderness (1966) and Lovers (1969) as “texts” that construct Soviet identity by dint of the recognition and acceptance of the ideal life model by the society. Since humans transform themselves and the world around them through an imitation, the main research questions are as follows: what social interaction features can be identified in these films? What is the appeal of the Soviet discourse and how is it transmitted in such seemingly “non-ideological” films? Ishmukhamedov’s films were studied as a semiotic system, in which the main myths and archetypes were revealed that had a manipulative and mobilizing influence on the viewer, thereby creating an image of a Soviet person which is attractive to the masses. The everyday life captured in these films symbolizes the stability and reliability of living in the USSR and Central Asia in the 1960s. After analyzing the figurative system of the Soviet-time everyday life in Ishmukhamedov’s films, the author finds out that identity is a system consisting of ethnic, cultural, age, natural, social, professional, mental, artifact identities, as well as the identity of the genus and small groups, which set the models and patterns of behavior for a Soviet person, which patterns were accepted and copied by the people.